PedWiz: a web-based tool for pedigree informatics - Song, Yeunjoo E.; Elston, Robert C. (Frontiers in Genetics, 2013)
A novel web-based tool PedWiz that pipelines the informatics process for pedigree data is introduced. PedWiz is designed to assist researchers in the analysis of pedigree data. It provides a convenient tool for pedigree informatics: descriptive statistics, relative pairs, genetic similarity coefficients, the variance-covariance matrix for three estimated coefficients of allele identical-by-descent sharing as well as mean allele sharing, a plot of the pedigree structures, and a visualization of the identity coefficients. With a renewed interest in linkage and other family-based methods, PedWiz will be a valuable tool for the analysis of family data.